Prognostic Implications of Low Level Cardiac Troponin Elevation Using High‐Sensitivity Cardiac Troponin T - Grinstein, Jonathan (Clin Cardiol, 2015)
BACKGROUND: High‐sensitivity cardiac troponin T (hsTnT) is used in many countries, but is not available in the United States. Prior evidence has been viewed as inconclusive as to whether low cardiac troponin T (cTnT) concentrations detected with hsTnT are prognostically meaningful compared with fourth‐generation cTnT. HYPOTHESIS: The aim of this study was to assess the prognostic performance of low‐level cTnT elevations using the hsTnT assay compared with the assay (fourth‐generation) currently available in the United States. METHODS: We measured serum cTnT in 4160 patients with non–ST‐elevation acute coronary syndrome using both the hsTnT and fourth‐generation assays. Patients were stratified at the 99th percentile cut point for each assay. RESULTS: Patients with baseline hsTnT ≥14 ng/L (n = 3697) vs <14 ng/L were at higher 30‐day risk of cardiovascular death (CVD) or myocardial infarction (MI) (9.1% vs 1.9%, P < 0.0001). After adjusting for all other elements of the Thrombolysis In Myocardial Infarction risk score, hsTnT ≥14 carried a 5.2‐fold higher risk of CVD/MI (95% confidence interval [CI]: 2.6‐10.1, P < 0.0001). Low levels of hsTnT (14–50 ng/L) also revealed increased risk (CVD/MI: 6.4%, P = 0.002). Importantly, patients with negative fourth‐generation cTnT but positive hsTnT were at 4.5‐times higher risk of CVD/MI (95% CI: 1.9‐11.0, P = 0.0008) than patients with negative hsTnT. In contrast, patients with a negative hsTnT but positive fourth‐generation cTnT result had a lower rate of CVD/MI than with a positive hsTnT (1.3% vs 8.2%, P = 0.0005). CONCLUSIONS: Low‐level increases in cTnT detected using the hsTnT assay identified patients at a meaningfully higher risk and who might otherwise be missed, and improves upon risk stratification using the cTnT assay currently available in the United States.